The determinant of cost efficiency of Islamic bank in Malaysia / Nurul Nagiha Sapuan - Sapuan, Nurul Nagiha (2016)
Aim of this study is to examine the cost efficiency of Islamic Bank in Malaysia. Through this chapter, it will be discussing on background of the study, problem statement, research objectives, significance of study, scope of study and variables used in this study.